Inmunolocalización del sistema Angiopoyetina-1/Tie-2 en placentas de cabras - Mura, N. (2019)
Angiopoietin-1 and Tie-2 receptor participate in the process of angiogenesis and thus plays a critical role in fetal growth and development, affecting neonatal survival and growth. The objective of this study was to describe the structural changes and determine the location of the Angiopoietin-1/Tie-2 system in goat placentas at different gestational stages. Histological sections from placentas of 50, 100 and 135 days of gestation were used. This were immunolocatization with an anti-Ang-1 antibody and with anti-Tie-2. Ang-1 was evidenced in the trophoblastic epithelium in intense form in placentas of 50 and 100 days of gestation and in a weaker form in the maternal epithelium and fetal blood vessels. In contrast, in placentas of 135 days of gestation, the immunolocatization was intense on the maternal epithelium and weak on the fetal and endothelial tissue. The Tie-2 receptor was located in the endothelial cells of fetal and maternal capillaries and in the trophoblastic epithelium in the periods analyzed. This would indicate that the Angiopoietin-1/Tie-2 system acts by an autocrine and paracrine mechanism of action on angiogenesis, in addition to the main angiogenic factor, vascular endothelial growth factor.